Districts and networks in the digital generation music scene in Mexico City. Issue 1 (2nd January 2017) - Mercado-Celis, Alejandro
ABSTRACT: The identification of aestheticized urban districts with music scenes is a simplification of economic and cultural processes that take place at the metropolitan region and not at the urban district scale. Creative urban districts are a component of larger systems that include diverse consumers from different social classes with diverse tastes, many of whom come from places that are not as glamorous or trendy as hip neighbourhoods. These other urban areas and the producers and consumers of cultural products in those areas tend to be forgotten or dismissed as unimportant. Exploring the spatial patterns of creative clusters at the intra-urban level is relevant for a better understanding of the role of central and peripheral districts in the functioning of these industries. Using social network analysis, this research spatializes Mexico City's local digital generation music scene and reveals a metropolitan-wide network of venues and bands. Policy implications targeting the network of venues and bands are discussed.